(3GdYhdeI h JCKjQGJgG aj GdeLJeY GdYQHj (B/s - (3NeT, eLO GdOjfs ((3YeGf(B: s (3OGQ eLOdGhj(B, s, 2011)
(3JMdjd HfhO h eHGOF GJaGbjI GdLGJ h GdhUhd Gdi age eJYeb ddYhdeI fXQG dOhQ gPg GdGJaGbjI GdeMhQj aj fThA h JOYje GdYhdeI h YedjGJgG h eDSSGJgG eY GdGgJeGe HJMdjd Jdc GdHfhO GdJj JhaQ GSJKfGAGJ ddOhd GdfGejI h ef VefgG GdOhd GdYQHjI dJecjf gPg GdOhd ef GYGOI JQJjH ChVGYgG HeG jVef dgG OQLI efGSHI ef GdNUhUjI GdGbJUGOjI h GdKbGajI , JMdjd BKGQ GdYhdeI Ydi GdeLJeY GdYQHj GbJUGOjG h GLJeGYjG h JMdjd JOGYjGJ GdYhdeI Ydi GdOhdI aj GdeLJeY GdYQHj h NGUI ajeG jJYdb HGdJYOjdGJ Ydi COhGQgG HJbHdgG ddeTGQcI aj GdSjGOI GdKbGaI Ydi ehGWfjgG HYO JRGjO GdaVGFjGJ h NOeGJ GdGfJQfjJ dG SjeG Cf OhQ GdOhdI CUHM ef LOjO eMW GdGgJeGe hOdc HYO JOGYjGJ GdCReI GdeGdjI GdYGdejI GdJj HOGJ aj fgGjI YGe (B2008s
(3LOGhd GMUGFjI U(B.9s
Keywords: (3GdEbJUGO(B- (3HdOGf GdYQHjIs; (3GdYhdeI(B- (3GdHdOGf GdYQHjIs